Sonographic characteristics of local soft tissue recurrence in primary bone tumor and diagnostic efficacy versus MRI - Ping Yu; Junxue Gao; Yue Hu; Jiaan Zhu; Yu Wang (BMC Cancer)
Abstract Background The accurate diagnosis of local soft tissue recurrence (LR) in primary bone tumors is crucial for guiding clinical management and predicting patient outcomes. However, standardized postoperative surveillance protocols remain undefined. This study aims to compare the diagnostic efficacy of ultrasound (US) versus magnetic resonance imaging (MRI) in detecting LR following primary bone tumor surgery and to characterize the sonographic features of osteosarcoma recurrence. Methods We conducted a retrospective review of medical records from patients who underwent postoperative surveillance for primary bone tumors at our institution between 01/06/2016 to 01/09/2023. Diagnostic performance was compared using McNemar's test for paired variables. Sonographic characteristics were analyzed using logistic regression analysis, with statistical significance set at p < 0.05. Results Comparative analysis revealed no statistically significant differences (p > 0.05) in sensitivity, specificity, or accuracy between MRI and US, and the exact values for these parameters are provided in Table 1. Key sonographic features predictive of osteosarcoma recurrence included tumor size and anatomical location. The diagnostic model demonstrated excellent discriminative ability, with an area under the receiver operating characteristic (ROC) curve of 0.973. The diagnostic parameters were as follows: sensitivity (96.6%), specificity (90.9%), accuracy (94.6%), positive predictive value (95.0%), and negative predictive value (93.8%). Conclusion The findings from this study support the role of ultrasonography as a valuable tool in tumor surveillance paradigms, providing a scientific rationale for optimizing integrated management strategies in bone oncology.